Versatile clinical application of radial artery perforator flap for hand and wrist reconstruction - Jovanović, Mladen; Nikolić, Jelena; Komarčević, Aleksandar; Mijatović-Jovanović, Vesna; Stojičić, Milan; Bjelan, Sveto (Vojnosanitetski pregled, 2023)
Background/Aim. Radial artery perforator flap (RAPF) is a type of fasciocutaneous or adipofascial reverse pedicle flap, which proved to be a versatile flap for the reconstruction of small and moderate size soft tissue defects of the forearm, wrist, and hand. RAPF provides suitable skin coverage with elastic subcutaneous tissue thus enabling the protection of exposed or damaged functional structures and their simultaneous repair. The aim of this study was to summarize and analyze the results of the treatment of patients with upper extremity soft tissue defects caused by trauma, infection, burn, or tumor removal, which were reconstructed with RAPF. Methods. This retrospective study included 20 consecutive patients with skin and soft tissue defects of the hand and wrist, treated at the University Clinical Center of Vojvodina from 2012 to 2022. The design of the flaps and length of the pedicles were determined by the recipient site. Tourniquet-induced exsanguination was used during surgery for better visualization. The flaps were elevated and placed at the site of the defect. Data on patients and flaps were summarized upon their collection. Results. Distally based fasciocutaneous RAPF was used in all cases. The average age of the patients was 48 years, predominantly (64%) males. Defects were most often localized on the dorsal part of the hand (60%) and wrist (20%). The most common indications for surgery were trauma (45%) and tumor resection (25%). A satisfactory coverage of the defect was achieved in all 20 patients with no flap loss. Venous congestion was noted in 4 (20%) patients, which resulted in partial necrosis of the flap in 3 (15%) patients. Wound healing was achieved upon conservative treatment by secondary intention in two patients and with a secondary suture in the last one. A surgical site infection occurred in 2 (10%) patients who withdrew after proper local and systemic therapy. Conclusion. RAPF proved to be a workhorse flap for soft tissue reconstruction of the upper limb. This surgical solution led to an excellent functional and aesthetic outcome in the majority of patients. Complex surgical procedures could be done simultaneously, together with the reconstruction of tendons, joints, or fracture stabilization. The reliability and safety of these flaps are confirmed through our clinical data.
Keywords: hand; radial artery; surgical flaps; surgical procedures, reconstructive; wrist joint